The comparison of effectivity from consortium bio fertilizer and endophytic bio fertilizer on productivity and health of clone mature GMB 7 tea crop - Mieke Rochimi Setiawati; Restu Wulansari; Eko Pranoto (Research Institute for Tea and Cinchona, 2014)
This study aimed at comparing the effectiveness of consortium bio-fertilizer with endophytic bio fertilizer to increasing productivity and health of mature clone GMB 7 tea crop. This research was carried out at the Gambung Experimental Station Block A7 Research Institute for Tea and Cinchona, from July 2013 to September 2013. Randomized block design was used in this study with ten treatments and three replications i.e.: A1H0 = anorganic fertilizer (75%), A2H0 = anorganic fertilizer (50%), A1H1 = anorganic fertilizer (75%) + 2 liter consortium bio fertilizer, A1H2 = anorganic fertilizer (75 %) + 4 liter consortium bio-fertilizer, A2H1 = anorganic fertilizer (50 %) + 2 liter consortium bio fertilizer, A2H2 = anorganic fertilizer (50%) + 4 liter consortium bio-fertilizer, A1H3 = anorganic fertilizer (75 %) + 2 liter endophytic bio fertilizer, A1H4 = anorganic fertilizer (75%) + 4 liter endophytic bio fertilizer, A2H3 = anorganic fertilizer (50%) + 2 liter endophytic bio fertilizer and A2H4 = anorganic fertilizers (50%) +4 liter endophytic bio fertilizer. The results showed there were a significantly difference on amount of the pekoe shoot among treatments, although the others variable was not significantly different. However, the overall consortium bio-fertilizer resulted in the production of shoots 15,36% and endophytic biofertilizer application resulted in the production of shoots 21,93% higher than the control (without bio fertilizer). When compared to the first plucking, the number of shoot from July to September showed increasing trend, so did the number of banji shoots.